Draft Annual Plan 2005-2006 Volume-I (Narrative) - Planning Commission (Planning Commission, 2005)
Rajasthan, with a total geographical area of 3,42,239.74 sq. kms. is the largest State in the country. It was formed as a State of the Union of India in March 1949, by the merger of 19 Principalities and two Chiefships, with Ajmer-Merwara being added in 1956 on the recommendations of the States Reorganization Commission. Administratively, Rajasthan is divided today into 6 divisions and 32 districts, which are further sub-divided into 188 sub-divisions, 241 tehsils and 237 development blocks. 1.2 The population of Rajasthan, standing at 5.65 crore 2001 Census) and a density of 165 persons per sq. km., recorded a decadal growth rate of 28.41 percent over the population of 4.40 crores (1991 Census) and a density of 129 persons per sq. km. The SC population in the State stood at 17.2% of the total and that of ST at 12.6%.
Narrative
Government of Rajasthan